Mejora de pronóstico de una bodega de repuestos de electrodomésticos a través de la metodología six sigma - Nuñez Miranda, Fernando David (2009)
The Multinational Company that deals with electronics and others products has different branchs from all around the world. One of them is in Ecuador with more than 10 years in market with a local warehouse of spare parts which provide solution to the demand generated by the maintenance and technical service of guarantee and other commercialized products in the country. The methodology Six Sigma is being implemented in offices, departments and plants of production all around the world. The offices in Ecuador have proposed a project to improve the efficiency of the forecasting of supply the warehouse. The objective of the project is the implementation of a forecasting system that allows the improvement of efficiency of the warehouse, with a 20% to 30% in cost reduction without affecting the level of service. Following the methodology of Six Sigma, they hope to have reduction in the amount of inventory, to increase the index of rotation, to improve they capacity of availability and to enhance the quality of service.